Demonstration Methods to Improve Intensive Reading Skills in 3rd-Grade Students - Muhammad Yusnan; Karim; Risman Iye; Asriani Abbas; Sumiaty (International Journal of Learning Reformation in Elementary Education, 2022)
The problem in this study is how to improve intensive reading skills in Indonesian subjects using the demo method in 3rd-grade students. The purpose of this study was "to improve intensive reading skills through demonstration methods in Indonesian subjects in 3rd grade student of an elementary school in Baubau city, Indonesia. This research is a classroom action research consisting of two cycles. Each cycle consisted of one meeting. The data was quantitative one obtained through learning outcomes tests. The qualitative data obtained through observation sheets. Based on the results of data analysis, it was concluded that the application of the demo method could improve the ability to read intensively fairy tale material for 3rd-grade student. The average learning ourcome of procycle was 54.77, and learning completeness is 22.72%. The average one of 1st cycle was 62.5 and learning completion was 45.45%. The average learning outcomes score of 2nd was 86.13 and completeness learn 100%. It means that the learning activity improved student performance.